2016
DOI: 10.1186/s12961-016-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of health research impact in Iran

Abstract: BackgroundIn recent years, Iran has made significant developments in the field of health sciences. However, the question is whether this considerable increase has affected public health. The research budget has always been negligible and unsustainable in developing countries. Hence, using the Payback Framework, we conducted this study to evaluate the impact of health research in Iran.MethodsBy using a cross-sectional method and two-stage stratified cluster sampling, the projects were randomly selected from six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Further examples of studies of the impact of multi-project programmes have been published since the second review was conducted, with the examples from Bangladesh, Brazil, Ghana and Iran [25] illustrating a widening interest in producing evidence of impact. In the Ghanaian example, 20 out of 30 studies were used to contribute to action, and Kok et al again showed that considerable levels of impact could be achieved by adopting an interactive approach; they reported that “ the results of 17 out of 18 user-initiated studies were translated into action ” ([4], p. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further examples of studies of the impact of multi-project programmes have been published since the second review was conducted, with the examples from Bangladesh, Brazil, Ghana and Iran [25] illustrating a widening interest in producing evidence of impact. In the Ghanaian example, 20 out of 30 studies were used to contribute to action, and Kok et al again showed that considerable levels of impact could be achieved by adopting an interactive approach; they reported that “ the results of 17 out of 18 user-initiated studies were translated into action ” ([4], p. 1).…”
Section: Discussionmentioning
confidence: 99%
“…While much of the evidence on the benefits of research came originally from high-income countries, interest in producing such evidence is spreading globally, with examples from Bangladesh [2], Brazil [3], Ghana [4] and Iran [5] published in 2015–2016. Studies typically identify the impacts of health research in one or more of categories such as health policy, clinical practice, health outcomes and the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impressive surge of research publications, various studies have suggested that Iran’s research activities in health are not well aligned with the structure of the country’s disease burden and the health needs of its population [ 7 - 9 ]. These studies propose that a key problem might lie in the absence of a systematic process of health research prioritization that engages both the knowledge producers (ie, researchers) and users (ie, policy makers and members of the wider society) [ 8 ].…”
mentioning
confidence: 99%
“…For instance, since 1996, GERD began to be specified in Iran’s annual national budget plan, which has relatively improved transparency in financing and has allowed monitoring the investments in research [ 83 ]. Furthermore, several papers have reported that, in recent years, some major macro-policy documents had set targets for substantial rises in R&D expenditure, although the targets were not eventually met [ 15 , 89 ]. An apparent example of failure was the target of increasing GERD to 2.5% by 2015, whereas the last retrieved GERD was only 0.3% (in 2014) [ 15 ].…”
Section: Resultsmentioning
confidence: 99%